Islamophobia as a Global Narrative A Philosophy of Science Critique of the Production of Religious Knowledge - Zarkoni (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2025)
Islamophobia has emerged as a global issue shaping public perceptions of Muslim communities through knowledge construction and narrative dominance. This study aims to analyze how Islamophobia is produced as a global narrative through mechanisms of religious knowledge and its epistemological implications. The research employs a qualitative approach with a critical case study design, involving 12–15 informants, including academics, media practitioners, and community leaders. It utilizes in-depth interviews, media and document observation, and archival documentation. Findings indicate that Islamophobia is constructed through selective information, epistemic bias, and the politicization of knowledge; global media emphasizes conflict and extremism, while political and ideological interests influence religious epistemology. The study’s novelty lies in applying a philosophy-of-science perspective to examine knowledge production. Practical implications include the need for media literacy, critical education, and intervention strategies to reduce negative stereotypes and strengthen interfaith dialogue.